IMAGE GUIDED FNAC OF HEPATOBILIARY LESIONS WITH RADIOLOGICAL CORRELATION. - PRERNA CHHABRA; SARITA NIBHORIA; SAHIL CHHABRA; SHIVANI PURI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The clinical and radiological presentations of both primary and metastatic hepatobiliary tumours can be similar–as a space occupying focal mass. FNAC can play a decisive diagnostic role minimizing the requirement of biopsy. Therefore, the present study was undertaken to evaluate various hepatic and gall bladder lesions on the basis of their cytomorphological features upon Ultrasound/CT guided FNAC and to study their correlation with radiological findings. Methods: The patients presenting with liver enlargement, gall bladder masses, radiologic evidence of focal/diffuse and nodular hepatic lesions were subjected to ultrasound guided fine needle aspiration, which was performed using 22-gauge lumbar puncture needle with 20/50 cc disposable syringe under ultrasound/CT guidance. Subsequently smears were fixed and stained according to standard protocol and cytomorphological examination was done in the department of pathology. Analytical tests (Mc-nemar’s test for p-value and kappa test test for kappa value) were applied for cytological and radiological correlation. Results: Among 100 patients, liver lesions accounted for 79 cases and gallbladder lesions accounted for 21 cases. On FNAC, liver lesions were categorized into 91.23% cases of neoplastic lesions, 6.33% as non-neoplastic lesions and 2.53% as indeterminate/non-diagnostic cases. Radiological-cytological correlation was seen in 43/79 cases (54.43%). Gall bladder lesions were categorized into 9.52% as non-neoplastic, 85.71% as neoplastic and 4.77% as indeterminate/non-diagnostic. Radiological-cytological correlation was seen in 7/21 cases (31.25%). Conclusion: Radiologically guided fine needle aspiration is a very useful test in diagnosing liver and gall bladder lesions as it is simple to perform, cost-effective, safe and a quick procedure leading to early diagnosis.